The contribution of Hassan al-Rammah to gunpowder and rocket technology - Ahmed Ghazal, Belal; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective of this chapter is to study the early development of gunpowder and rocket technologies in the golden age of the Islamic civilization contributed by aI-Hassan AIRammah and understand his methodology in developing the military sciences and technologies. The methodology adopted in this chapter is a library based research and data is collected from reliable sources and internet sources. The research investigates the role of Hassan al Rammah in developing the rocket technology in the 13th century. The main focus of the research is to highlight the stages of the development of such a technology and how it was utilized by the Muslims in their war against the Mongols and the crusades during the 13th . The research explores the technique was used by Al -Rammah for developing rocket fuel and suitable Gunpowder recipes for cannons, rocket and fireworks. The significance of this research comes from revealing al Hassan al -Rammah effort in developing weaponry and military's techniques that helped the Muslim to excel in the military technology during the golden age of the Islamic civilization. AI-Hassan AIRammah (the lancer), a Muslim scholar lived in Syria in the thirteenth century, and died in between 1294-1295A.D AI- Rammah excelled in the military field, he wrote 107 recipes of gunpowder that had been used for rocket, canons and fireworks [Hassan, 2003,p.23]. He wrote treaties entitled: AI-Furusiyya wa AI-Manasib AI-Harbiyya (Book of Military Horsemanship and Ingenious War Devices) [Zaky, 1967, pA8]. This chapter explores al Hassan al-Rammah's endeavour in developing the rocket technology